Gender, Academic Rank, Employment Status, University Type and Job Stress among University Academic Staffs in Pahang, Malaysia and Jogjakarta, Indonesia Context - Ahmad, Othman; Safaria, Triantoro; Muhammad Nubli, Abdul Wahab (Universiti Malaysia Pahang, 2012)
The purpose of this study is to investigate the relationship between demographic variables with job stress among university academic staffs. The demographic variables of this study are gender, academic rank, employment status, and university type. The quantitative survey study was used to focus on comparation between Malaysia and Indonesia context. Data are collected from 343 university academic staffs from Pahang, Malaysia and 337 university academic staffs from Jogjakarta, Indonesia.The analysis of variance test (ANOVA) was used to test the study hypothesis in each nation. The results showed that gender, university type, and academic status were predictors of job stress in Pahang and Jogjakarta academicians. Employment status had a significant effect on job stress just among Jogjakarta academic staffs, but not for Pahang academic staffs. This study is the first crosscultural research that examines the effect of demographic variables on job stress among university academic staffs in Pahang, Malaysia and Jogjakarta, Indonesia. Besides, the study confirmed existing theory and expanded the applicability of work-related stressors in a cross national context.